Диспозиционная модель психологического механизма политической самоидентификации индивида - Резник, А. (Социология: теория, методы, маркетинг, 2001)
The author considers the phenomenon of an individual's political self-identification as a starting point for the formation of political self-consciousness. The principal mechanisms of political identity formation in connection with the personality attitudes and dispositions are represented. The interactions of political self-consciousness levels — ideological, generalized and situational — are traced, as well as the conditions of the irformation.